NON-ALCOHOLIC FATTY LIVER DISEASE (NAFLD): METABOLIC MECHANISMS AND RISK OF PROGRESSION TO CIRRHOSIS (International journal of medical sciences, 2026)
Non-alcoholic fatty liver disease (NAFLD) is a prevalent chronic liver disorder characterized by excessive fat accumulation in hepatocytes in the absence of significant alcohol consumption. It is strongly associated with obesity, insulin resistance, type 2 diabetes mellitus, and metabolic syndrome. NAFLD encompasses a spectrum ranging from simple steatosis to non-alcoholic steatohepatitis (NASH), fibrosis, and eventually cirrhosis. Pathophysiology involves multiple metabolic mechanisms including insulin resistance, oxidative stress, lipid peroxidation, inflammatory cytokine production, and mitochondrial dysfunction. Early identification of at-risk individuals, non-invasive assessment of fibrosis, and targeted interventions are crucial to prevent progression. Therapeutic strategies focus on lifestyle modification, management of metabolic comorbidities, pharmacologic therapies under investigation, and emerging treatments targeting hepatic inflammation and fibrosis. This article reviews the metabolic mechanisms underlying NAFLD, risk factors for progression to cirrhosis, diagnostic strategies, and current and emerging therapeutic approaches.